Analysis of Financial Results of Business Entities - Kuatbaevich, Ismailov Timur (Miasto Przyszłości, 2025)
The financial performance of business entities plays a crucial role in economic stability and growth. This study examines the financial results of enterprises, particularly analyzing profitability indicators based on national accounting standards and international financial reporting systems. A significant gap exists in adapting global financial assessment methods to national accounting frameworks, leading to inconsistencies in evaluating business performance. The study employs a combination of scientific observation, comparative analysis, factor analysis, and descriptive statistical methods to assess the profitability trends of a selected enterprise over a five-year period. The findings reveal a downward trend in net profit, with enterprises facing challenges in managing production costs and financial liabilities. The results indicate that without cost optimization and improved financial management, businesses may experience long-term instability and potential bankruptcy. The study highlights the need for enhanced financial strategies, including better cost management, revenue diversification, and policy reforms to ensure economic sustainability. These findings contribute to a broader understanding of financial analysis methodologies and their implications for business entities in emerging economies.